Effect of Side Chain Length Change of Polycarboxylate-Ether-Based High-Range Water-Reducing Admixture on Properties of Cementitious Systems Containing Fly Ash - Altun, M.G.; Özen, Süleyman; Mardani-Aghabaglou, A. (American Society of Civil Engineers (ASCE), 2021)
In this study, the effect was investigated of side chain length changes of polycarboxylate-ether-based high-range water-reducing (HRWR) admixture on fresh properties, compressive strength, and water adsorption capacity of cementitious systems. For this aim, three HRWR admixtures having same raw materials, anionic/nonionic group ratio, free nonionic group content, and main chain length but different side chain length and molecular weight were synthesized. The effect was investigated of the mentioned admixtures on the properties of mixtures containing 0%, 15%, 30%, and 45% of fly ash. According to the test results, regardless of fly ash utilization ratio, the flowability of the mixtures was positively affected with the increase of the water-reducing admixture side chain length to a certain value. However, utilization of admixtures having the longer side chain length than a certain value adversely affected the flow properties of the mixtures. It is thought that this situation is due to the reduction of the admixture efficiency (steric effect) by increasing the possibility of intertwining of polymers of admixture having higher side chain length. The admixture with 2,400 g/mol of side chain molecular weight (length) showed the best performance in terms of fresh properties. The change of HRWR admixture properties had no significant effect on the strength and water adsorption capacity of the mixtures. Moreover, regardless of HRWR admixture properties, the time-dependent flowability of the mixtures was adversely affected and the water adsorption capacity was decreased with the utilization of fly ash. This effect was more pronounced with increasing replacement ratio of fly ash. © 2021 American Society of Civil Engineers.
Keywords: Admixture side chain; Cement paste; Fly ash; Mortar; Polycarboxylate-ether-based high-range water reducing admixture